Amorphous carbonized objects and their contribution to reconstructing ancient Mesoamerican cuisine: An innovative non-destructive methodological approach - Clarissa Cagnato; Nawa Sugiyama; Laura Longo; Alessandro Bonetto; Matteo Parisatto; Elena Longo; Marko Prasek; Giuliana Tromba; Antonio Marcomini; Elena Badetti (PLoS ONE, 2025)
Archaeobotanists often come across small, amorphous carbonized objects (ACOs) in their flotation samples. Although their identification remains difficult and requires a range of characterization techniques, the study of ACOs recovered from sites in Europe and the Levant have allowed researchers to reconstruct ancient recipes. However, similar materials from sites in pre-Hispanic Central America have been overlooked, hampering our understanding of their ancient cooking traditions. This article proposes a new pipeline to study such remains through three types of non-destructive imaging techniques: optical microscopy (OM), scanning electron microscopy (SEM), and synchrotron radiation-based phase-contrast X-ray computed microtomography (SR micro-CT), key techniques to consider for the imaging of archaeological materials. The approach was developed by establishing a reference collection from modern foods based on traditional ingredients (e.g., maize, manioc) used in the region of interest. This pipeline was then tested on archaeological samples from the ancient site of Teotihuacan (Mexico), which successfully captured the presence of the remains of complex, multi-component food preparations from a feasting context. To the best of our knowledge, this is the first time in which the combination of imaging techniques has been used to discriminate between actual food remains, or simply seeds or plant parts in archaeological contexts from Prehispanic Central America. This study allows to shed more light on ancient recipes and culinary traditions and can be applied more broadly to other contexts in Mesoamerica.